Intranasal Administration of 2/6-Rotavirus-Like Particles with Mutant Escherichia coli Heat-Labile Toxin (LT-R192G) Induces Antibody-Secreting Cell Responses but Not Protective Immunity in Gnotobiotic Pigs - Yuan, Lijuan (American Society for Microbiology (ASM), 2000)
We investigated the immunogenicity of recombinant double-layered rotavirus-like particle (2/6-VLPs) vaccines derived from simian SA11 or human (VP6) Wa and bovine RF (VP2) rotavirus strains. The 2/6-VLPs were administered to gnotobiotic pigs intranasally (i.n.) with a mutant Escherichia coli heat-labile toxin, LT-R192G (mLT), as mucosal adjuvant. Pigs were challenged with virulent Wa (P1A[8],G1) human rotavirus at postinoculation day (PID) 21 (two-dose VLP regimen) or 28 (three-dose VLP regimen). In vivo antigen-activated antibody-secreting cells (ASC) (effector B cells) and in vitro antigen-reactivated ASC (derived from memory B cells) from intestinal and systemic lymphoid tissues (duodenum, ileum, mesenteric lymph nodes [MLN], spleen, peripheral blood lymphocytes [PBL], and bone marrow lymphocytes) collected at selected times were quantitated by enzyme-linked immunospot assays. Rotavirus-specific immunoglobulin M (IgM), IgA, and IgG ASC and memory B-cell responses were detected by PID 21 or 28 in intestinal and systemic lymphoid tissues after i.n. inoculation with two or three doses of 2/6-VLPs with or without mLT. Greater mean numbers of virus-specific ASC and memory B cells in all tissues prechallenge were induced in pigs inoculated with two doses of SA11 2/6-VLPs plus mLT compared to SA11 2/6-VLPs without mLT. After challenge, anamnestic IgA and IgG ASC and memory B-cell responses were detected in intestinal lymphoid tissues of all VLP-inoculated groups, but serum virus-neutralizing antibody titers were not significantly enhanced compared to the challenged controls. Pigs inoculated with Wa-RF 2/6-VLPs (with or without mLT) developed higher anamnestic IgA and IgG ASC responses in ileum after challenge compared to pigs inoculated with SA11 2/6-VLPs (with or without mLT). Three doses of SA 11 2/6-VLP plus mLT induced the highest mean numbers of IgG memory B cells in MLN, spleen, and PBL among all groups postchallenge. However, no significant protection against diarrhea or virus shedding was evident in any of the 2/6-VLP (with or without mLT)-inoculated pigs after challenge with virulent Wa human rotavirus. These results indicate that 2/6-VLP vaccines are immunogenic in gnotobiotic pigs when inoculated i.n. and that the adjuvant mLT enhanced their immunogenicity. However, i.n. inoculation of gnotobiotic pigs with 2/6-VLPs did not confer protection against human rotavirus challenge.